PENGARUH KARAKTERISTIK TUJUAN ANGGARAN,GOOD GOVERNANCE, DAN PENGAWASAN APIP TERHADAP KINERJA APARAT PEMERINTAH DAERAH KABUPATEN BENGKALIS - Indah Syurgawi; Restu Agusti; Al Azhar Ali (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to analyze the effect of budget participation, budget goal clarity, feedback, budget evaluation, good governance and oversight APIP the performance of local government officials Bengkalis. This research is a survey research. Where the data obtained from questionnaires distributed to respondents. Data distributed and collected by purposive sampling technique. The sample used in this study is the head of the public, personnel and chief financial officer of each department in Bengkalis with a total of 90 respondents. The type of data used are primary data collection method of data using questionnaires. Data analysis method used in this study is multiple regression with SPSS version 21.The results showed that the performance of local government officials does not affect the implementation of good governance. Local financial management affect the implementation of good governance. Internal control systems of government affect the implementation of good governance. Based on the calculation of the coefficient of determination (R2) obtained a value of 0,711. This shows that the influence of the independent variables on the dependent 71.1% and the remaining 28.9% influenced by other variables.Keywords: Budget, Characteristics, Good Governance, Oversight APIP Authorities, Local Government, and Performance.